2014
DOI: 10.1016/j.socscimed.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Social support, social strain and inflammation: Evidence from a national longitudinal study of U.S. adults

Abstract: Social relationships have long been held to have powerful effects on health and survival, but it remains unclear whether such associations differ by function and domain of relationships over time and what biophysiological mechanisms underlie these links. This study addressed these gaps by examining the longitudinal associations of persistent relationship quality across a ten year span with a major indicator of immune function. Specifically, we examined how perceived social support and social strain from relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 53 publications
8
114
0
2
Order By: Relevance
“…It has been shown that family support significantly influences the health and welfare of people (15). Equally, family and friends provide emotional and material support and share knowledge for welfare and health (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that family support significantly influences the health and welfare of people (15). Equally, family and friends provide emotional and material support and share knowledge for welfare and health (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Relationship deficits-such as social isolation, lack of support, or high strain-are alternative forms of social adversity that can create chronic stress by continuous exposure to chains of risk that accumulate over the life course (27,28). Individuals who experienced early adversity are subject to multiple and longer durations of stress exposures and more prone to inflammatory and stress-related diseases as they age.…”
Section: Significancementioning
confidence: 99%
“…Healthy individuals who reported receiving less support from their friends, families, and spouses had higher levels of several inflammatory markers over the course of 5 years than those who reported more support [51]. In the MESA study, adults with lower social support had higher levels of CRP than those with higher social support [52].…”
Section: Biopsychosocial Risk Factors For Elevated Inflammationmentioning
confidence: 99%